2002
DOI: 10.1161/hs0402.105555
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Therapy of Transient Focal Cerebral Ischemia

Abstract: Background and Purpose-To study whether intravascular or hemodynamic factors contribute to the marked neuroprotective effect of albumin therapy in focal cerebral ischemia, 2 complementary methods were applied: laser-scanning confocal microscopy (LSCM) and laser-Doppler perfusion imaging (LDPI). Methods-In the LSCM study, Sprague-Dawley rats were anesthetized with halothane/nitrous oxide, and a cranial window was placed over the dorsolateral frontoparietal cortex. Rats received 2-hour middle cerebral artery occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 57 publications
5
86
1
Order By: Relevance
“…Similar to our findings with PNA, SOD administration reduced early postresuscitation hyperemia in an asphyxial CA model in dogs (Cerchiari et al, 1987), and administration of SOD-albumin complex improved blood flow and neurologic outcome in a global ischemia-reperfusion model (Takeda et al, 1993). Similar to our study, albumin was shown to improve cortical perfusion after permanent focal cerebral ischemia (Liu et al, 2001) and improved perfusion in the microcirculation during the postischemic reperfusion period (Belayev et al, 2002). One possible explanation for our findings is mitigation of superoxide-induced vascular dysfunction by PNA versus albumin.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to our findings with PNA, SOD administration reduced early postresuscitation hyperemia in an asphyxial CA model in dogs (Cerchiari et al, 1987), and administration of SOD-albumin complex improved blood flow and neurologic outcome in a global ischemia-reperfusion model (Takeda et al, 1993). Similar to our study, albumin was shown to improve cortical perfusion after permanent focal cerebral ischemia (Liu et al, 2001) and improved perfusion in the microcirculation during the postischemic reperfusion period (Belayev et al, 2002). One possible explanation for our findings is mitigation of superoxide-induced vascular dysfunction by PNA versus albumin.…”
Section: Discussionsupporting
confidence: 87%
“…A beneficial effect of albumin in neurologic pathologies is suggested by studies in stroke and traumatic brain injury in which lower serum albumin levels are associated with poor outcome (Bernard et al, 2008;Idicula et al, 2009). Albumin has beneficial effects in animal models of focal ischemia (Belayev et al, 1997(Belayev et al, , 2002Liu et al, 2001); however, it was not found to be neuroprotec- tive either in a neonatal model of stroke or after clinical traumatic brain injury in adults (Myburgh et al, 2007;Wang et al, 2007). Albumin's beneficial effects for focal ischemia-reperfusion are attributed to antioxidant properties, inhibition of copper-induced peroxidation, fatty acid oxidation Rowley et al, 1984;Yao et al, 2010), binding of fatty acids and heme, and early upregulation of vascular endothelial growth factor (Yao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other agents such as basic fibroblast growth factor (bFGF) (Kawamata et al, 1997), albumin treatment has been proposed to preserve the blood-brain barrier and contribute to stroke recovery via neuroprotective properties. In particular, albumin has been clearly shown to improve microvascular hemodynamics and to exert proendothelial effects (Belayev et al, 2002). In this study, we test whether delayedalbumin treatment improves the overall outcome of recovering ischemic brains using functional magnetic resonance imaging (fMRI) to characterize the treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia results in vascular abnormalities, such as hyperemia, residual hypoperfusion (Uhl et al, 2000;Belayev et al, 2002;Pulsinelli et al, 1983), and microcirculatory dysfunction (Clavier et al, 1994;Cipolla et al, 1997;Pulsinelli et al, 1982). Striking endothelial defects in vasodilation and constriction have been described (Rosenblum, 1988;Dietrich, 1994;Rosenblum and Wormley, 1995;Cipolla et al, 1997;Watanabe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%